ACTUAL PROBLEMS OF ACCOUNTING OF CONCESSION ASSETS AND LIABILITIES IN THE REPUBLIC OF KAZAKHSTAN - Ussabayev Arman; Caroline Aggestam Pontoppidan; Ussabayev Damir (Scientific Journal of Pedagogy and Economics, 2019)
This research considers issues of accounting update in public sector of the economy of the Republic of Kazakhstan under the conditions of the development of public-private partnership in form of concessionary agreement. The accounting procedures of concessionary objects, concessionary commitments, profits and losses in accordance with International public sector accounting standards (IPSAS) and International financial reporting standards (IFRS) are reviewed and recommendations on problems of concessionary contract recording are provided.